Ligustilide Attenuates Ischemia Reperfusion-Induced Hippocampal Neuronal Apoptosis via Activating the PI3K/Akt Pathway - Qian Wu; Qian Wu; Zhiguo Mao; Jiao Liu; Jinling Huang; Ning Wang; Ning Wang (Frontiers Media S.A., 2020)
Ligustilide (LIG), a main lipophilic component isolated from Cnidii Rhizoma (Cnidium officinale, rhizome) and Angelicae Gigantis Radix (Angelica gigas Nakai, root), has been shown to alleviate cerebral ischemia injury and paly a neuroprotective role. We investigated mechanisms underlying the antiapoptotic effects of LIG in vitro and in vivo, respectively, using cultured primary hippocampal neurons under oxygen-glucose deprivation/reperfusion (OGD/R) and rats under cerebral ischemia reperfusion(I/R) conditions. In vitro studies revealed that the suppressed apoptosis in hippocampal neurons upon LIG treatment was associated with reduced calcium influx and generation of reactive oxygen species. The LIG-treated hippocampal neurons exhibited decreased the ratio of Bax/Bcl-2, and the release of CytC from mitochondria as well as the expression of cleaved caspase-3, which were accompanied with enhanced the phosphorylation of Akt protein, in a PI3K-dependent manner. In vivo studies demonstrated a neuroprotective role of LIG in attenuating cerebral infarction volume, neurological injury and hippocampal neuron injury, suggesting that LIG could reverse ischemia reperfusion(I/R)-induced apoptosis of hippocampal neurons. These results together suggest that LIG may be considered as a neuroprotectant in the treatment of ischemia stroke.